New subgenus and new species Nousia (Araucophlebia) latifolia subgen. n. et sp. n. (Ephemeroptera: Leptophlebiidae) from Chile - Kluge, Nikita J. (Zootaxa, 2014)
A new subgenus and new species, Nousia (Araucophlebia) latifolia subgen. et sp.n., are described from the Maule and Araucania regions in Chile, based on male and female imagos reared from larvae. This species has unusual shapes of larval tergalii, male imaginal genitalia and flat eggs.